Instructional Leadership and Spiritual-Based Academic Supervision in Strengthening School Religious Culture - Muhammad Rifqi (Program Studi Doktor Manajemen Pendidikan Islam, Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study examines the integration of instructional leadership and spiritual-based academic supervision in fostering a substantive religious culture within Islamic elementary education. Using a qualitative approach, the research analyzes how supervisory mechanisms are transformed from administrative control into a comprehensive spiritual mentoring process. The findings reveal that the synergy between academic supervision and spiritual leadership creates a religious climate through daily habituation, the integration of Islamic values into the curriculum, and the implementation of a 'hidden curriculum.' Furthermore, the study identifies that adaptive leadership strategies and ecosystem synergy between the school and parents are crucial in overcoming urban environmental barriers. The results demonstrate that this holistic supervision model significantly enhances students' religious character and elevates public trust in the institution. This research contributes to the discourse on educational leadership by positioning spiritual values as the core of academic oversight to achieve long-term character transformation.